Prenatal detection of chromosome aneuploidies in uncultured chorionic villus samples by FISH. - Bryndorf, T. (1996)
We developed a 1-d FISH assay for detection of numerical chromosome abnormalities in uncultured chorionic villus samples (CVS). Probes specific for chromosomes 13, 18, 21, X, and Y were used to determine ploidy by analysis of signal number in hybridized nuclei. Aneuploidy detection using this assay was directly compared with the results obtained by conventional cytogenetic analysis in a consecutive, clinical study of 2,709 CVS and placental samples. The FISH assay yielded discrete differences in the signal profiles between cytogenetically normal and abnormal samples. On the basis of these results, we generated FISH-assay cutoff values that discriminated between karyotypically normal and aneuploid samples. Samples with mosaicism and a single sample with possible heritable small chromosome X probe target were exceptions and showed poor agreement between FISH results and conventional cytogenetics. We conclude that the FISH assay may act as a more accurate and less labor-demanding alternative to "direct" CVS analysis.